Health-related quality of life impact in a randomised phase III study of the combination of dabrafenib and trametinib versus dabrafenib monotherapy in patients with BRAF V600 metastatic melanoma. Issue 7 (May 2015) - Schadendorf, Dirk; Amonkar, Mayur M.; Stroyakovskiy, Daniil; Levchenko, Evgeny; Gogas, Helen; de Braud, Filippo; Grob, Jean-Jacques; Bondarenko, Igor; Garbe, Claus; Lebbe, Celeste; Larkin, James; Chiarion-Sileni, Vanna; et al.
Abstract Aim To present the impact of treatments on health-related quality of life (HRQoL) from the double-blind, randomised phase III COMBI-d study that investigated the combination of dabrafenib and trametinib versus dabrafenib monotherapy in patients with BRAF V600E/K-mutant metastatic melanoma. COMBI-d showed significantly prolonged progression-free survival for the combination. Methods HRQoL was evaluated using the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire-C30, a generic cancer questionnaire (completed at baseline, during study treatment, at progression and post progression) assessing various dimensions (global health/QoL, functional status, and symptom impact). A mixed-model, repeated-measures analyses of covariance evaluated differences between arms. Results Questionnaire completion rates were >95% at baseline, >85% to week 40 and >70% at disease progression. Baseline scores across both arms were comparable for all dimensions. Global health dimension scores were significantly better at weeks 8, 16 and 24 for patients receiving the combination during treatment and at progression. The majority of functional dimension scores (physical, social, role, emotional and cognitive functioning) trended in favour of the combination. Pain scores were significantly improved and clinically meaningful (6–13 point difference) for patients receiving the combination for all follow-up assessments versus those receiving dabrafenib monotherapy. For other symptom dimensions (nausea and vomiting, diarrhoea, dyspnoea, and constipation), scores trended in favour of dabrafenib monotherapy. Conclusion This analysis demonstrates that the combination of dabrafenib and trametinib provides better preservation of HRQoL and pain improvements versus dabrafenib monotherapy while also delaying progression. (Clinicaltrials.gov registration number: NCT01584648).